Experimental Observation of the Spectral Gap in Microwave n-Disk Systems - Barkhofen, Sonja; Weich, Tobias; Potzuweit, A.; Stöckmann, H.-J.; Kuhl, U.; Zworski, M. (Physical Review Letters)
Keywords: General Physics and Astronomy

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Post-selection free, integrated optical source of non-degenerate, polarization entangled photon pairs - Herrmann, Harald; Yang, Xu; Thomas, Abu; Poppe, Andreas; Sohler, Wolfgang; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef U.; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Silberhorn, Christine; Leuchs, Gerd; Marquardt, Christoph (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Increasing the Dimensionality of Quantum Walks Using Multiple Walkers - Rohde, Peter P.; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Gilchrist, Alexei; Silberhorn, Christine (Journal of Computational and Theoretical Nanoscience)
Keywords: Electrical and Electronic Engineering; Computational Mathematics; Condensed Matter Physics; General Materials Science; General Chemistry

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

A 2D Quantum Walk Simulation of Two-Particle Dynamics - Schreiber, Andreas; Gábris, Aurél; Rohde, Peter P.; Laiho, Kaisa; Štefaňák, Martin; Potoček, Václav; Hamilton, Craig; Jex, Igor; Silberhorn, Christine (Science)
Here, There, Everywhere Random walks are a powerful mathematical method that can be used to simulate certain processes in biology, chemistry, or even the stock market. They present a statistical method for mapping the possible routes that processes can take. Quantum walks are expected to be able to probe multiple paths simultaneously. Quantum walks have been demonstrated for one-dimensional, or straight-line, walks. Now, Schreiber et al. (p. 55 , published online 8 March) demonstrate an optical system that can simulate quantum walks over a two-dimensional system, thereby providing the capability of describing much more complex processes.
Keywords: Multidisciplinary

Limits on the deterministic creation of pure single-photon states using parametric down-conversion - Christ, Andreas; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

High resolution time-to-space conversion of sub-picosecond pulses at 155µm by non-degenerate SFG in PPLN crystal - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Photon Propagation in a Discrete Fiber Network: An Interplay of Coherence and Losses - Regensburger, Alois; Bersch, Christoph; Hinrichs, Benjamin; Onishchukov, Georgy; Schreiber, Andreas; Silberhorn, Christine; Peschel, Ulf (Physical Review Letters)
Keywords: General Physics and Astronomy

Decoherence and Disorder in Quantum Walks: From Ballistic Spread to Localization - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Testing spectral filters as Gaussian quantum optical channels - Laiho, K.; Christ, A.; Cassemiro, K. N.; Silberhorn, Christine (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

High-performance single-photon generation with commercial-grade optical fiber - Söller, Christoph; Cohen, Offir; Smith, Brian J.; Walmsley, Ian A.; Silberhorn, Christine (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Realistic g (2) measurement of a PDC source with single photon detectors in the presence of background - Eckstein, Andreas; Christ, Andreas; Mosley, Peter J.; Silberhorn, Christine (physica status solidi c)
Keywords: Condensed Matter Physics

Highly Efficient Single-Pass Source of Pulsed Single-Mode Twin Beams of Light - Eckstein, Andreas; Christ, Andreas; Mosley, Peter J.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Probing multimode squeezing with correlation functions - Christ, Andreas; Laiho, Kaisa; Eckstein, Andreas; Cassemiro, Katiúscia N; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Multi-walker discrete time quantum walks on arbitrary graphs, their properties and their photonic implementation - Rohde, Peter P; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Probing the Negative Wigner Function of a Pulsed Single Photon Point by Point - Laiho, Kaisa; Cassemiro, Katiúscia N.; Gross, David; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Accessing the purity of a single photon by the width of the Hong–Ou–Mandel interference - Cassemiro, Katiúscia N; Laiho, Kaisa; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Photons Walking the Line: A Quantum Walk with Adjustable Coin Operations - Schreiber, A.; Cassemiro, K. N.; Potoček, V.; Gábris, A.; Mosley, P. J.; Andersson, E.; Jex, I.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Accessing Higher Order Correlations in Quantum Optical States by Time Multiplexing - Avenhaus, M.; Laiho, K.; Chekhova, M. V.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Optimized generation of heralded Fock states using parametric down-conversion - Brańczyk, Agata M; Ralph, T C; Helwig, Wolfram; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Continuous-variable quantum information processing - Andersen, U.L.; Leuchs, G.; Silberhorn, Christine (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Quantum Key Distribution with Bright Entangled Beams - Silberhorn, Ch.; Korolkova, N.; Leuchs, G. (Physical Review Letters)
Keywords: General Physics and Astronomy